ARTIFICIAL NEURAL NETWORK PREDICTION OF ASPHALTENE PRECIPITATION IN CRUDE OILS - YIP, THANG FOONG (2021)
Asphaltene is a compound that is found in crude oils. Its molecular structure is hard to be identified due to its complex molecular structure, but it known that it has certain composition of sulphur and it will poison the catalyst used in the chemical processes also will increase the energy consumption in crude oils transporting and separation systems.